2020
DOI: 10.2147/cmar.s230138
|View full text |Cite
|
Sign up to set email alerts
|

<p>Contrast-Enhanced CT Parameters of Gastric Adenocarcinoma: Can Radiomic Features Be Surrogate Biomarkers for HER2 Over-Expression Status?</p>

Abstract: These authors contributed equally to this workObjective: The aim of this study was to determine the role of contrast-enhanced computed tomography (CE-CT) parameters in predicting the expression status of HER2 in gastric adenocarcinoma (GAC) patients before radical gastrectomy. Materials and Methods: A total of 460 GAC patients who underwent non-contrast CT (NC-CT) and CE-CT examinations before radical resection were enrolled in this retrospective study. The radiologists reviewed their CT scans and recorded par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Other investigators have used a D-TA approach to predict the response to neoadjuvant chemotherapy in resectable locally advanced gastric cancer and found that the TA parameter GLCM-contrast was able to predict complete pathologic response with an AUC of 0.763 [129]. Finally, innovative approaches have used radiomics for a non-invasive assessment of the immune microenvironment, correlating the TA features with the Treg cell infiltration or the HER2 expression [130,131].…”
Section: Texture Analysis and Prognosis-focus On Gastric Cancermentioning
confidence: 99%
“…Other investigators have used a D-TA approach to predict the response to neoadjuvant chemotherapy in resectable locally advanced gastric cancer and found that the TA parameter GLCM-contrast was able to predict complete pathologic response with an AUC of 0.763 [129]. Finally, innovative approaches have used radiomics for a non-invasive assessment of the immune microenvironment, correlating the TA features with the Treg cell infiltration or the HER2 expression [130,131].…”
Section: Texture Analysis and Prognosis-focus On Gastric Cancermentioning
confidence: 99%
“…Radiomics can decode tumor heterogeneity noninvasively, and there is a potential correlation between tumor genotypes and CT-based radiomics characteristics (30,31). In the study of contrast-enhanced CT parameters of gastric adenocarcinoma, Wang et al (32) found that radiomic features can be surrogate biomarkers for HER2 over-expression Status. Yang et al (33) used deep radiomics features from CT images to evaluate the HER2 status of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is an emerging discipline that combines traditional medical image knowledge with big data analysis and precision medicine ( 29 ). Radiomics can decode tumor heterogeneity noninvasively, and there is a potential correlation between tumor genotypes and CT–based radiomics characteristics ( 30 , 31 ). In the study of contrast-enhanced CT parameters of gastric adenocarcinoma, Wang et al ( 32 ) found that radiomic features can be surrogate biomarkers for HER2 over-expression Status.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been some studies on the association between radiomic features and HER2 status (22-24, 26, 29-31). Several studies investigated the relationship between HER2 status and radiomic features in gastric cancer and colorectal cancer (29)(30)(31). Li et al (29) built and validated a CT-based radiomics nomogram for HER2 status prediction, which showed good performance.…”
Section: Discussionmentioning
confidence: 99%